LDC7559 inhibits microglial activation and GSDMD-dependent pyroptosis after subarachnoid hemorrhage - Cai, Wenhua; Wu, Zhe; Lai, Jinqing; Yao, Jieran; Zeng, Yile; Fang, Zhongning; Lin, Weibin; Chen, Junyan; Xu, Chaoyang; Chen, Xiangrong (Frontiers in Immunology, 2023)
Mounting evidence indicates that inhibition of microglial activation and neuronal pyroptosis plays important roles in brain function recovery after subarachnoid hemorrhage (SAH). LDC7559 is a newly discovered gasdermin D (GSDMD) inhibitor. Previous studies have demonstrated that LDC7559 could inhibit microglial proliferation and pyroptosis. However, the beneficial effects of LDC7559 on SAH remain obscure. Based on this background, we investigated the potential role and the mechanism of LDC7559 on SAH-induced brain damage both in vivo and in vitro. The findings revealed that microglial activation and neuronal pyroptosis were evidently increased after SAH, which could be markedly suppressed by LDC7559 both in vivo and in vitro. Meanwhile, LDC7559 treatment reduced neuronal apoptosis and improved behavior function. Mechanistically, LDC7559 decreased the levels of GSDMD and cleaved GSDMD after SAH. In contrast, nod-like receptor pyrin domain-containing 3 (NLRP3) inflammasome activation by nigericin increased GSDMD-mediated pyroptosis and abated the beneficial effects of LDC7559 on SAH-induced brain damage. However, LDC7559 treatment did not significantly affect the expression of NLRP3 after SAH. Taken together, LDC7559 might suppress neuronal pyroptosis and microglial activation after SAH by inhibiting GSDMD, thereby promoting brain functional recovery.